Understanding Family Tourism: A Perspective of Bibliometric Review - Qiao, Guanghui; Cao, Yating; Chen, Qingwen; Jia, Qiaoran (Frontiers in Psychology, 2022)
The study performed bibliometric visual analyses of family tourism research literature from 2008 to 2021, revealing the knowledge evolution process, research focuses, and future trends in this field. A total of 132 articles on family tourism were collated from the SSCI database of the Web of Sciences core collection and analyzed by CiteSpace. The results show that the number of research studies on family tourism has increased from 2008 to 2021, however, the overall base is small. Purdue University has the highest number of publications and citations. Inter-country cooperation occurs between the US, China, the UK, and Australia. Recently, “motivation” and “benefit” have become hot topics in family tourism research, and “social tourism” has received widespread attention, revealing future research directions. Lehto and Wu are the core figures in the family tourism field, and their achievements have been highly cited and peer-recognized. This study focuses on family tourism research in different cultural situations, enriching the knowledge system of family tourism research, and encouraging future family tourism research focus more on seniors and disadvantaged families.